Titanium niobate silicon-based composite material and preparation method and application thereof
By preparing titanium-niobate silicon-based composite materials, using electrospinning and chemical reactions to form a three-dimensional network structure, and through gas heating treatment, the problems of large expansion and low conductivity of silicon-based composite materials are solved, and the specific capacity and efficiency of the battery are improved.
Patent Information
- Application Number
- CN202211704142.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing silicon-based composite materials expand greatly during charging and discharging, and the electronic conductivity is low, resulting in limited improvements in battery specific capacity and first-time efficiency.
Using the preparation method of titanium silicon niobate-based composite material, carbon fiber material containing niobium titanium cerium is obtained by electrospinning, and reacted with carboxylated nanosilicon and silane coupling agent in an alkaline solution to form a three-dimensional network structure. Then heating is carried out under the atmosphere of a modified gas and a carbon source gas to obtain a titanium silicon niobate composite material.
It effectively reduces the expansion of the material, improves the ionic conductivity, the specific capacity and first-time efficiency of the battery, and improves the liquid retention rate, liquid absorption rate and circulation performance.
Smart Images

Figure CN116014101B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery materials, and in particular to a titanium niobate silicon-based composite material and a preparation method and application thereof. Background Art
[0002] The negative electrode material of lithium-ion batteries is the main body of lithium storage. During the charge and discharge process of lithium-ion batteries, lithium ions are repeatedly embedded and extracted from the negative electrode material, and electrochemical oxidation / reduction reactions occur. At present, the negative electrode materials used in commercial lithium-ion batteries are mainly carbon-based materials, but the theoretical capacity of carbon-based negative electrodes is limited. In the future market that requires higher battery energy density, carbon-based materials cannot meet the requirements.
[0003] Silicon-based materials have become a hot topic in the research of negative electrode materials for lithium-ion batteries due to their huge stable theoretical capacity. Although silicon-based materials have extremely high energy density and are the preferred materials for negative electrode materials for lithium-ion batteries, silicon-based materials have defects such as large expansion during charging and discharging and poor electronic conductivity, which limit their widespread application in the field of power batteries. The measures to reduce the expansion of silicon-based materials mainly include nano-sizing, pore formation, and morphology change, and element doping and coating are used to reduce the electronic conductivity of the material and increase the ion diffusion coefficient.
[0004] In the prior art, a layer of amorphous carbon is usually coated on the outer layer of the silicon base to improve the overall electronic and ionic conductivity of the material. However, the silicon-based material still has a large expansion capacity, and the improvement in the electronic conductivity of the material and the specific capacity and initial efficiency of the battery is limited. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing silicon-based composite materials, such as large expansion and limited improvement in the electronic conductivity of the material and the specific capacity and initial efficiency of the battery, thereby providing a titanium niobate silicon-based composite material and its preparation method and application.
[0006] The present invention provides a method for preparing a titanium niobate silicon-based composite material, comprising the following steps:
[0007] 1) After mixing a titanium source, a niobium source, an organic cerium compound, an organic polymer and an organic solvent, the obtained mixed solution is subjected to electrostatic spinning to obtain a carbon fiber material containing niobium, titanium and cerium;
[0008] 2) mixing carboxylated nano-silicon, a silane coupling agent and an organic solvent, and then adding the carbon fiber material containing niobium, titanium and cerium obtained in step 1) and an alkali solution to react to obtain a niobium, titanium, cerium and silicon-based carbon fiber material;
[0009] 3) subjecting the niobium-titanium-cerium-silicon-based carbon fiber material obtained in step 2) to a first heating in a modified gas atmosphere, and then subjecting it to a second heating in a carbon source gas atmosphere to obtain the titanium niobate-silicon-based composite material;
[0010] The modified gas is selected from at least one of fluorine, chlorine, ammonia and sulfur dioxide.
[0011] Preferably, in step 1), the mass ratio of the total mass of the titanium source and the niobium source to the mass of the organic cerium compound, the organic polymer, and the organic solvent is 100:(1-10):(50-200):(400-2000);
[0012] The titanium source is selected from at least one of Ti(OC4H9)4 and TiO2, and the niobium source is selected from at least one of NbCl5 and Nb2O5; wherein the molar ratio of the titanium source to the niobium source is 1:(0.5-2);
[0013] The organic polymer includes at least one of polyacrylonitrile, polymethyl methacrylate and polyvinyl pyrrolidone; the molecular weight of the organic polymer is 100,000 to 1.5 million;
[0014] The organic cerium compound is selected from at least one of cerium acetate, cerium propionate and cerium acetylacetonate hydrate.
[0015] Preferably, during electrospinning in step 1), the voltage is 5-50 kV, the roller receiving speed is 0-100 r / min, the pushing speed is 0.1-10 mL / h; the distance from the electrospinning needle to the receiver is 5-30 cm, and the electrospinning time is 30-300 min.
[0016] Preferably, in step 1), the diameter of the carbon fiber material containing niobium, titanium and cerium is 1-10 μm.
[0017] Preferably, in step 2), the mass ratio of carboxylated nano-silicon, silane coupling agent, organic solvent, carbon fiber material containing niobium, titanium and cerium, and alkaline solution is 100:(1-10):(50-500)(10-50):(100-500);
[0018] The particle size of carboxylated nanosilicon is 100-500nm;
[0019] The silane coupling agent includes at least one of γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, vinyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane;
[0020] The alkali solution includes at least one of cyclohexylamine, dimethylamine, trimethylamine, diethylamine, triethylamine, ethylenediamine and ethanolamine.
[0021] Preferably, the reaction temperature in step 2) is 50-150° C. and the reaction time is 1-6 h.
[0022] Preferably, the flow rate of the modified gas is 1-500 sccm;
[0023] The first heating temperature is 300-500°C, and the holding time is 1-6h;
[0024] The organic solvent includes at least one of cyclohexane, acetic acid, acetic acid, oxalic acid, tartaric acid and malic acid.
[0025] Preferably, in step 3), the carbon source gas includes at least one of methane, acetylene and natural gas, and the flow rate of the carbon source gas is 1-10 sccm;
[0026] The second heating temperature is 800-1200° C., and the time is 1-6 hours.
[0027] Optionally, the preparation method of carboxylated nanosilicon includes: mixing and stirring nanosilicon, concentrated sulfuric acid, concentrated hydrochloric acid, and hydrofluoric acid, then filtering, washing with deionized water, and vacuum drying to obtain carboxylated nanosilicon, wherein the addition ratio of nanosilicon, concentrated sulfuric acid, concentrated hydrochloric acid, and hydrofluoric acid is 100: (300-800): (300-800): (300-800), and the unit of ratio is g / ml / ml / ml; the concentration of concentrated sulfuric acid is 70-80wt%, the concentration of concentrated hydrochloric acid is 35-38wt%, the concentration of hydrofluoric acid is 0.1-2wt%, and the stirring time is 12-24h.
[0028] The present invention also provides a titanium niobate silicon-based composite material, which is prepared by the above-mentioned preparation method.
[0029] The present invention also provides a lithium ion battery, comprising the titanium niobate silicon-based composite material described above.
[0030] The technical solution of the present invention has the following advantages:
[0031] 1. The present invention provides a method for preparing a titanium niobate silicon-based composite material, comprising the following steps: 1) electrospinning an organic solution containing a titanium source, a niobium source, an organic cerium compound and a dispersant to obtain a carbon fiber material containing niobium, titanium and cerium; 2) mixing carboxylated nano-silicon and a silane coupling agent and reacting the mixture with the carbon fiber material containing niobium, titanium and cerium obtained in step 1) in an alkaline solution to obtain a niobium, titanium and cerium carbon fiber silicon-based carbon fiber material; 3) calcining the niobium, titanium and cerium carbon fiber silicon-based carbon fiber material obtained in step 2) under the action of a modified gas, and then continuing to calcine under the action of a carbon source gas to obtain the titanium niobate silicon-based composite material.
[0032] The present invention electrostatically spins a mixed solution of a titanium source, a niobium source, an organic cerium compound, an organic polymer and an organic solvent, and then adds an organic cerium compound to the mixed solution to obtain a carbon fiber material containing niobium, titanium and cerium. The doping of cerium can reduce impedance on the one hand, and cerium itself has a high specific capacity on the other hand, which is conducive to obtaining a carbon fiber material containing niobium, titanium and cerium with low impedance and high specific capacity. At the same time, carboxylated nano-silicon, a silane coupling agent and an organic solvent are mixed, and then the carbon fiber material containing niobium, titanium and cerium and an alkali solution are added to react. The carbon fiber material containing niobium, titanium and cerium is coated on the surface of the nano-silicon to form a three-dimensional network structure. On the one hand, the pores left by the three-dimensional network structure are used to reduce expansion, and on the other hand, the low expansion rate of the fibrous structure itself is used to reduce material expansion. Compared with inorganic cerium doping, doping with organic cerium compounds has mild reaction conditions, and the nitrogen and carbon left after the organic cerium compounds are carbonized can reduce impedance and reduce expansion; then the obtained niobium titanium cerium-coated silicon-based carbon fiber material is heated in a modified gas atmosphere to reduce the defects of the titanium niobate material finally obtained, thereby improving the electronic conductivity of the titanium niobate material, and finally heated in a carbon source gas atmosphere for carbon coating to obtain the titanium niobate-coated silicon-based composite material; the titanium niobate silicon-based composite material obtained by the method of the present invention can effectively reduce the expansion of the material, improve the ionic conductivity of the material as well as the specific capacity and first efficiency of the battery, and the material obtained by the present invention also has excellent liquid retention rate, liquid absorption rate and cycle performance.
[0033] 2. The method for preparing the titanium niobate silicon-based composite material provided by the present invention, further, the organic cerium compound is selected from at least one of cerium octylbenzene sulfonate, cerium acetate, cerium propionate and cerium acetylacetonate. The present invention can further ensure that the obtained titanium niobate silicon-based composite material has low expansion by using the above-mentioned specific organic cerium compound for doping, which can effectively improve the ionic conductivity of the material and the specific capacity and first efficiency of the battery, and at the same time ensure that the material obtained by the present invention also has excellent liquid retention rate, liquid absorption rate and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is a scanning electron microscope image of the titanium niobate silicon-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0038] The preparation method of carboxylated nano-silicon used in Examples 1-3 is as follows: 100 g of nano-silicon is added to a mixed solution of 500 ml of concentrated sulfuric acid (concentration of 70 wt%), 500 ml of concentrated hydrochloric acid (concentration of 36 wt%), and 500 ml of hydrofluoric acid (concentration of 1 wt%), and stirred for 24 h, then filtered, washed with deionized water, and vacuum dried to obtain carboxylated nano-silicon;
[0039] The natural gas used in Example 3 has a composition (volume fraction) of methane 92%, ethane 5%, propane 2.5%, and butane 0.5%.
[0040] Example 1
[0041] This embodiment provides a method for preparing a titanium niobate silicon-based composite material, comprising the following steps:
[0042] 1) 56 g of Ti(OC4H9)4 (0.165 mol), 44 g of Nb2O5 (0.166 mol), 5 g of hydrated cerium acetylacetonate, 100 g of polyacrylonitrile (molecular weight 100,000) and 800 ml of cyclohexane were mixed by ball milling, and the obtained mixed solution was electrospun for 60 min at a roller receiving speed of 50 r / min and a propulsion pushing speed of 5 mL / h under a voltage of 20 kV (the distance from the electrospinning needle to the receiver during the electrospinning process was 10 cm) to obtain a carbon fiber material containing niobium, titanium and cerium (with a diameter of 1 μm);
[0043] 2) adding 5 g of γ-chloropropyltrimethoxysilane to 100 ml of cyclohexane, then adding 100 g of carboxylated nano-silicon (particle size of 200 nm) and dispersing evenly, then adding 30 g of the carbon fiber material containing niobium, titanium, and cerium obtained in step 1) and 300 ml of cyclohexylamine and reacting at 100° C. for 3 h to obtain a niobium, titanium, cerium, and silicon-based carbon fiber material;
[0044] 3) The niobium-titanium-cerium-silicon-based carbon fiber material obtained in step 2) is placed in a tubular furnace, argon gas is introduced into the tubular furnace to exhaust the air in the tubular furnace, and then fluorine gas is continuously introduced into the tubular furnace at a flow rate of 6 sccm, and the niobium-titanium-cerium-silicon-based carbon fiber material is heated in a fluorine atmosphere at a heating temperature of 400°C for a holding time of 3 hours, and then the fluorine gas is replaced with methane, and methane gas is introduced into the tubular furnace at a flow rate of 6 sccm, and the tubular furnace is heated, and the silicon-based niobium-titanium-cerium carbon fiber material is continuously heated at 1000°C for 3 hours, and then argon gas is introduced into the tubular furnace to cool it to room temperature, and it is crushed to obtain the titanium niobate silicon-based composite material.
[0045] Example 2
[0046] This embodiment provides a method for preparing a titanium niobate silicon-based composite material, comprising the following steps:
[0047] 1) 12.9 g of TiO2 (0.162 mol), 87.1 g of NbCl5 (0.322 mol), 1 g of cerium acetate, 50 g of polymethyl methacrylate (molecular weight 100,000) and 500 ml of acetic acid were mixed by ball milling, and the obtained mixed solution was electrospun for 30 min at a roller receiving speed of 10 r / min and a propulsion pushing speed of 10 mL / h under a voltage of 5 kV (the distance from the electrospinning needle to the receiver during the electrospinning process was 5 cm) to obtain a carbon fiber material containing niobium, titanium and cerium (with a diameter of 1 μm);
[0048] 2) 1 g of vinyl trichlorosilane was added to 100 ml of acetic acid, and then 100 g of carboxylated nano silicon (with a particle size of 100 nm) was added and dispersed evenly, and then 10 g of the carbon fiber material containing niobium, titanium, and cerium obtained in step 1) and 100 ml of dimethylamine were added and reacted at 50° C. for 6 hours to obtain a niobium, titanium, cerium, and silicon-based carbon fiber material;
[0049] 3) The niobium-titanium-cerium-silicon-based carbon fiber material obtained in step 2) is placed in a tubular furnace, argon gas is introduced into the tubular furnace to exhaust the air in the tubular furnace, and then chlorine gas is continuously introduced into the tubular furnace at a flow rate of 1 sccm, and the niobium-titanium-cerium-silicon-based carbon fiber material is heated in a chlorine atmosphere at a heating temperature of 300°C for a holding time of 3 hours, and then the chlorine gas is replaced with acetylene, and acetylene gas is introduced into the tubular furnace at a flow rate of 1 sccm, and the tubular furnace is heated, and the silicon-based niobium-titanium-cerium carbon fiber material is continuously heated at 800°C for 3 hours, and then argon gas is introduced into the tubular furnace to cool it to room temperature, and it is crushed to obtain the titanium niobate silicon-based composite material.
[0050] Example 3
[0051] This embodiment provides a method for preparing a titanium niobate silicon-based composite material, comprising the following steps:
[0052] 1) 13.1 g of TiO2 (0.164 mol), 86.9 g of Nb2O5 (0.327 mol), 10 g of cerium propionate, 200 g of polyvinyl pyrrolidone (molecular weight 100,000) and 1000 ml of malic acid were mixed by ball milling, and the obtained mixed solution was electrospun for 30 min at a roller receiving speed of 100 r / min and a propulsion pushing speed of 10 mL / h under a voltage of 50 kV (the distance from the electrospinning needle to the receiver during the electrospinning process was 30 cm) to obtain a carbon fiber material containing niobium, titanium and cerium (with a diameter of 10 μm);
[0053] 2) adding 10 g of vinyltrimethoxysilane to 500 ml of xylene, then adding 100 g of carboxylated nano-silicon (particle size of 500 nm) and dispersing evenly, then adding 50 g of the carbon fiber material containing niobium, titanium, and cerium obtained in step 1) and 500 ml of triethylamine and reacting at 150° C. for 1 hour to obtain a niobium, titanium, cerium, and silicon-based carbon fiber material;
[0054] 3) placing the niobium-titanium-cerium-silicon-based carbon fiber material obtained in step 2) in a tubular furnace, introducing argon gas into the tubular furnace to exhaust the air in the tubular furnace, and then continuously introducing ammonia gas into the tubular furnace at a flow rate of 10 sccm, heating the niobium-titanium-cerium-silicon-based carbon fiber material in an ammonia atmosphere at a heating temperature of 500°C for a holding time of 1 hour, then replacing the ammonia gas with natural gas, introducing natural gas into the tubular furnace at a flow rate of 10 sccm, and heating the tubular furnace, continuing to heat the silicon-based niobium-titanium-cerium carbon fiber material at 1200°C for 3 hours, and then introducing argon gas into the tubular furnace to cool it to room temperature, and crushing it to obtain the titanium niobate silicon-based composite material.
[0055] Comparative Example 1
[0056] This comparative example provides a method for preparing a titanium niobate silicon-based composite material, which is different from Example 1 in that hydrated cerium acetylacetonate is not added in step 1).
[0057] Comparative Example 2
[0058] This comparative example provides a method for preparing a titanium niobate silicon-based composite material, which differs from Example 1 in that in step 3): the niobium titanium cerium silicon-based carbon fiber material obtained in step 2) is placed in a tubular furnace, argon gas is introduced into the tubular furnace to exhaust the air in the tubular furnace, and then methane gas is introduced into the tubular furnace at a flow rate of 6 sccm, and the tubular furnace is heated, and the silicon-based niobium titanium cerium carbon fiber material is continuously heated at 1000°C for 3 hours, and then argon gas is introduced into the tubular furnace to cool it to room temperature, and it is crushed to obtain the titanium niobate silicon-based composite material.
[0059] Comparative Example 3
[0060] This comparative example provides a method for preparing a titanium niobate silicon-based composite material, which is different from Example 1 in that in step 1), hydrated cerium acetylacetonate is replaced with cerium chloride (the molar number of cerium in both is the same).
[0061] Test Case
[0062] 1. Appearance
[0063] The titanium niobate silicon-based composite material prepared in Example 1 was tested by scanning electron microscopy (SEM). The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the titanium niobate silicon-based composite material presents a fibrous structure with a diameter of about 1 μm and a length of 50-200 μm.
[0064] 2. Button battery test
[0065] The titanium niobate silicon-based composite materials in Examples 1-3 and Comparative Examples 1-3 are used as negative electrode materials for lithium-ion batteries and assembled into button batteries. The preparation process includes:
[0066] Add binder, conductive agent and solvent to the negative electrode material of lithium-ion battery, stir to make slurry, coat on copper foil, dry and roll to get negative electrode sheet; the binder used is polyvinylidene fluoride (PVDF), the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), the amount ratio of negative electrode material, SP, PVDF and NMP is 95g:1g:4g:220mL; LiPF6 is electrolyte in the electrolyte, and the mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 is solvent; the metal lithium sheet is the counter electrode, and the diaphragm is polypropylene (PP) film. The button battery is assembled in an argon-filled glove box.
[0067] The electrochemical performance of button cells containing titanium niobate silicon-based composite materials of Examples 1-3 and Comparative Examples 1-3 was tested on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. At the same time, the powder conductivity of the material was tested by a four-probe tester, and the particle size, specific surface area, and tap density were tested in accordance with the national standard GBT-38823-2020 "Silicon Carbon". The test results are shown in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] It can be seen from the data in Table 1 that the specific capacity and the first efficiency of the titanium niobate silicon-based composite material prepared in the embodiment of the present invention are significantly better than those of the comparative example. It can be seen that the structural stability of the titanium niobate silicon-based composite material has been greatly improved.
[0072] At the same time, it can be found from the results of the powder conductivity that the electronic conductivity of the titanium niobate silicon-based composite material prepared in the embodiment of the present invention is greatly improved.
[0073] 3. Soft pack battery test:
[0074] The titanium niobate silicon-based composite materials in Examples 1-3 and Comparative Examples 1-3 were doped with 90% artificial graphite as negative electrode materials to prepare negative electrode sheets, and NCM532 was used as positive electrode material; LiPF6 was used as electrolyte in the electrolyte, and a mixture of EC and DEC with a volume ratio of 1:1 was used as solvent; Celgard 2400 membrane was used as a separator to prepare 5Ah soft-pack batteries. The liquid absorption and retention capacity of the negative electrode sheet, the full charge rebound of the electrode sheet, and the cycle performance were tested respectively.
[0075] a. Liquid absorption capacity test
[0076] Use a 1mL burette and draw 1mL of electrolyte, drip it on the surface of the electrode once, and count until the electrolyte is completely absorbed. Record the time t and calculate the liquid absorption rate V / t of the electrode. The test results are shown in Table 2.
[0077] b. Liquid retention rate test
[0078] According to the electrode parameters, the theoretical liquid absorption of the electrode m1 is calculated, and the weight of the electrode m2 is weighed. Then the electrode is placed in the electrolyte and soaked for 24 hours. The weight of the electrode is weighed as m3, and the liquid absorption of the electrode m3-m2 is calculated, and calculated according to the following formula: Liquid retention rate = (m3-m2)*100% / m1. The test results are shown in Table 2.
[0079] Table 2
[0080]
[0081] As can be seen from Table 2, the liquid absorption and liquid retention capacity of the titanium niobate silicon-based composite materials obtained in Examples 1-3 is significantly higher than that of the comparative example. The experimental results show that the titanium niobate silicon-based composite materials of the present invention have a high liquid absorption and liquid retention capacity. The reason may be that the material in the example has a high specific surface area, thereby improving the liquid absorption and liquid retention capacity of the material.
[0082] c. Electrode full charge rebound rate test
[0083] First, the thickness gauge was used to test the average thickness of the electrode sheet roll, which was D1. Then, the soft pack battery was fully charged to 4.2V, and then the battery was dissected, and the negative electrode sheet was taken out to test its thickness, which was D2. The thickness was calculated according to the following formula: electrode sheet full charge rebound rate = (D2-D1)*100% / D1. The test results are shown in Table 3.
[0084] d. Electrode resistivity test
[0085] The resistivity of the electrode was tested using a resistivity tester, and the test results are shown in Table 3.
[0086] Table 3
[0087]
[0088]
[0089] From the data in Table 3, it can be seen that the full-charge rebound rate and resistivity of the negative electrode sheet using the titanium niobate silicon-based composite material obtained in Examples 1-3 are significantly lower than those in Comparative Examples 1-3, that is, the negative electrode sheet made using the titanium niobate silicon-based composite material of the present invention has a lower full-charge rebound rate and resistivity. The reason may be that the embodiment electrode sheet is coated with a three-dimensional structure of a carbon fiber material containing niobium, titanium and cerium on the surface of nano-silicon. On the one hand, the fibrous structure is used to reduce expansion, and on the other hand, the pores left by the three-dimensional structure reduce expansion. At the same time, the embodiment material is doped with cerium with high electronic conductivity to reduce the resistivity of the electrode sheet.
[0090] e. Cycle performance test
[0091] The battery cycle performance was tested at a charge and discharge rate of 1C / 1C, a voltage range of 2.5V-4.2V, and a temperature of 25±3°C. The test results are shown in Table 4.
[0092] Table 4
[0093]
[0094] As can be seen from Table 4, the cycle performance of the battery made of the titanium niobate silicon-based composite material of the present invention is significantly better than that of the comparative example. The reason may be that the pole piece made of the titanium niobate silicon-based composite material of the present invention has a lower expansion rate, and the structure of the pole piece is more stable during the charge and discharge process, which improves its cycle performance. In addition, the titanium niobate silicon-based composite material of the present invention reduces surface defects through gas surface modification, improves compatibility with the electrolyte, and also improves its cycle performance.
[0095] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a titanium niobate silicon-based composite material, characterized in that: The steps include: 1) After mixing a titanium source, a niobium source, an organic cerium compound, an organic polymer and an organic solvent, the obtained mixed solution is subjected to electrostatic spinning to obtain a carbon fiber material containing niobium, titanium and cerium; 2) mixing carboxylated nano-silicon, a silane coupling agent and an organic solvent, and then adding the carbon fiber material containing niobium, titanium and cerium obtained in step 1) and an alkali solution to react to obtain a niobium, titanium, cerium and silicon-based carbon fiber material; 3) subjecting the niobium-titanium-cerium-silicon-based carbon fiber material obtained in step 2) to a first heating in a modified gas atmosphere, and then subjecting it to a second heating in a carbon source gas atmosphere to obtain the titanium niobate-silicon-based composite material; The modified gas is selected from at least one of fluorine, chlorine, ammonia and sulfur dioxide; Wherein, the organic cerium compound is selected from at least one of cerium acetate, cerium propionate and cerium acetylacetonate hydrate; The first heating temperature is 300-500°C, and the holding time is 1-6h; The second heating temperature is 800-1200° C., and the time is 1-6 hours.
2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of the total mass of the titanium source and the niobium source to the mass of the organic cerium compound, the organic polymer, and the organic solvent is 100:(1-10):(50-200):(400-2000); The titanium source is selected from at least one of Ti(OC4H9)4 and TiO2, and the niobium source is selected from at least one of NbCl5 and Nb2O5; wherein the molar ratio of the titanium source to the niobium source is 1:(0.5-2); The organic polymer includes at least one of polyacrylonitrile, polymethyl methacrylate and polyvinyl pyrrolidone; the molecular weight of the organic polymer is 100,000 to 1.5 million.
3. The preparation method according to claim 1, characterized in that: During electrospinning in step 1), the voltage is 5-50 kV, the roller receiving speed is 10-100 r / min, and the pushing speed is 0.1-10 mL / h; the distance from the electrospinning needle to the receiver is 5-30 cm, and the electrospinning time is 30-300 min.
4. The preparation method according to claim 1, characterized in that: Step 1) The diameter of the carbon fiber material containing niobium, titanium and cerium is 1-10 μm.
5. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of carboxylated nano-silicon, silane coupling agent, organic solvent, carbon fiber material containing niobium, titanium and cerium and alkaline solution is 100: (1-10): (50-500): (10-50): (100-500); The particle size of carboxylated nanosilicon is 100-500nm; The silane coupling agent includes at least one of γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, vinyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane; The alkali solution includes at least one of cyclohexylamine, dimethylamine, trimethylamine, diethylamine, triethylamine, ethylenediamine and ethanolamine.
6. The preparation method according to claim 1, characterized in that: In step 2), the reaction temperature is 50-150° C. and the reaction time is 1-6 h.
7. The preparation method according to claim 1, characterized in that: The flow rate of the modified gas is 1-500 sccm; The organic solvent includes at least one of cyclohexane, acetic acid, acetic acid, oxalic acid, tartaric acid and malic acid.
8. The preparation method according to claim 1, characterized in that: In step 3), the carbon source gas includes at least one of methane, acetylene and natural gas, and the flow rate of the carbon source gas is 1-10 sccm.
9. A titanium niobate silicon-based composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Including the titanium niobate silicon-based composite material as described in claim 9.
Citation Information
Patent Citations
Low-expansion silicon-carbon composite material and preparation method thereof
CN115207326A
Preparation method of high-energy-density silicon carbon / mesocarbon microsphere composite material
CN115207329A
Preparation method of lithium ion negative electrode composite material
CN115478341A